Hypocretin role in posttraumatic stress disorder-like behaviors induced by a novel stress protocol in mice - Lee, Tung-Yen; Yi, Pei-Lu; Chang, Fang-Chia (Frontiers in Psychiatry, 2023)
Introduction Posttraumatic stress disorder (PTSD) is a psychiatric disorder developed in individuals who expose to traumatic events. These patients may experience symptoms, such as recurrent unwanted memory of the traumatic event, avoidance of reminders of the trauma, increased arousal, and cognitive difficulty. The hypocretinergic system originates from the lateral hypothalamic area (LHA) and projects diffusely to the whole brain, and hypocretin may be involved in the features of stress-related disorder, PTSD. Methods Our study aimed to investigate the role of basolateral amygdala (BLA) hypocretin signals in the pathophysiology of PTSD-like symptoms induced by the modified multiple-prolonged stress (MPS) protocol. The BLA, a brain region involved in fear-related behaviors, receives the hypocretin projections. In this study, TCS1102, a dual hypocretin receptor antagonist, was used to block the hypocretin signal in BLA. Results Our data indicated that the MPS protocol is a potential PTSD-like paradigm in mice. Meanwhile, the blockade of hypocretin signaling in the BLA relieved the MPS-induced fear response, and partially reduced PTSD-like anxiety behaviors performed by the open field test (OFT) and elevated plus maze (EPM) task. Discussion Our findings suggest that the hypocretinergic system is a potential therapeutic approach for PTSD treatment. With further research, the hypocretin-based medication can be a candidate for human PTSD treatment.